0877 Impact of Sleep-Disordered Breathing on Quality of Life in Pediatric Cystic Fibrosis. (27th May 2020) - Shakkottai, A; Nasr, S Z; O'Brien, L M; Chervin, R D
Abstract: Introduction: The frequency of sleep-disordered breathing (SDB) may be high among children with cystic fibrosis (CF), a life-shortening, genetic disease that affects 1/3400 Caucasian live-births. Yet, the potential impact of SDB on their quality of life has not been well-studied. Methods: The Pediatric Sleep Questionnaire Sleep-Related Breathing Disorders (PSQ-SRBD) Scale, a well-validated SDB screening tool, and two validated quality-of-life questionnaires, the Pediatric Quality of Life Inventory (PedsQL™) and the Cystic Fibrosis Questionnaire-Revised (CFQ-R), were administered to children 6-17 years of age with CF consecutively during a 2-week period during routine pulmonary clinic visits. Results: Twenty-two children with CF and their parents completed the questionnaires. Mean age of the participants was 11.6±3.8(sd) years. Mean body mass index (BMI) percentile was 54.8±27.1%. Mean forced expiratory volume in 1 second percent predicted (FEV1 PPD) was 86.6±22.5%. Five subjects (23%) showed high risk for SDB (PSQ-SRBD Scores > 0.33). Seven additional subjects had PSQ-SRBD Scores of 0.3. Mean BMI percentile was higher among subjects with vs. without positive PSQ-SRBD Scores (66% vs. 42% respectively, p=0.03). The groups did not differ with regards to FEV1. Pearson/Spearman correlation identified negative associations between PSQ-SRBD Scores and functioning in multiple parent PedsQL domains: physical (R=-0.45, p=0.03), social (R=-0.53, p=0.01), school (R=-0.56, p=0.008); two child PedsQL domains: physical (R=-0.41, p=0.06), school (R=-0.41, p=0.06); multiple parent CFQ-R domains: physical (R=-0.44, p=0.08), respiratory (R=-0.45, p=0.07), emotional (R=-0.54, p=0.02), school (R=-0.70, p=0.002); and one child CFQ-R domain: physical (R=-0.51, p=0.01). None of these domains were associated with FEV1. Conclusion: Children with CF may have SDB symptoms independent of the extent of lung dysfunction. Although the current cross-sectional data cannot prove a causal effect, they raise the possibility that the SDB itself may have adverse impact on physical, emotional, social, and school functioning. Support: NIH Training Grant (F32HL145915)